Administration of Tepid Sponge with Hyperthermia to Children with Typhoid Fever in the Hospital - Tri Utami, Pegi; Rehana; Yunike (International Journal Scientific and Professional, 2022)
Typhoid fever is a disease that is often suffered by children, especially school-age children aged 5-14 years, because they spend a lot of time outside, especially at school, so children pay less attention to personal hygiene. Hyperthermia is a symptom that often appears in typhoid fever sufferers. To treat hyperthermia, you can use compresses, one of which is tepid sponge. This case study aims to reduce body temperature in children who experience hyperthermia. Method: This case study uses a descriptive design with a case study design, in the case of reducing body temperature using the tepid sponge technique through a nursing process approach carried out by researchers. Data collection in this study was by measuring the child's body temperature using a thermometer and comparing the results of body temperature measurements after the tepid sponge was carried out using a body temperature comparison sheet after and after the tepid sponge was carried out. Results: After implementing tepid sponge nursing, the results from patient I and patient II showed that body temperature improved to the normal range. Conclusion: Implementation of tepid sponge in patients with hyperthermia can be applied because it is effective in reducing body temperature